For Viral Reservoir Studies, Timing Matters. Issue 10 (October 2019) - Horsburgh, Bethany A.; Palmer, Sarah
Abstract : New strategies to eliminate persistent HIV-1 during therapy will benefit from animal models, such as non-human primates infected with simian immunodeficiency viruses (SIV) or chimeras (SHIV). Understanding the genetic composition of SIV and SHIV reservoirs during therapy is therefore crucial for the future application of this model.